California’s Senate Bill 596: Spearheading the global transition to sustainable cement - Kenneth C. Johnson (Next Sustainability)
The so-called “hard to abate” cement industry is at the cusp of a foundational technology transformation. Emerging technologies could make cement production carbon-neutral or carbon-negative, and could potentially do so profitably. California is well-positioned to spearhead the global transition to sustainable cement with its Senate Bill 596 (Becker 2021), which directs the California Air Resource Board (CARB) to “develop a comprehensive strategy for the state’s cement sector to achieve net-zero emissions of greenhouse gases associated with cement used within the state as soon as possible […]” CARB’s SB 596 strategy could serve as a model policy framework for other states’ and nations’ climate policies. This paper proposes a regulatory strategy for cement decarbonization, which includes carbon pricing and financing mechanisms to support and accelerate early-stage development and subsequent commercial adoption of sustainable cement technologies in California, pursuant to the broader goal of expediently decarbonizing the global cement industry.